Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
f(x) = 3ex - e
Step-by-step explanation:
In this equation we have basically the times e by 3x and -1
so first let's do e times 3x
here...
e X 3x = 3ex
so let's rewrite the equation
3ex - 1
now we times e by 1. (Note - Negative sign stays)
3ex - 1e
we don't have to write 1e cause 1e = e, they are the same.
Therefore the answer is 3ex - 1e
Following are the calculation of inverse:
Given:
[tex]\to f(x)=e^{3x-1}[/tex]
To find:
inverse function=?
Solution:
A function g is the inverse of function F if for [tex]y=f(x), x=g(y)[/tex]
[tex]\to y=e^{3x-1}[/tex]
Replacing the value of x with y
[tex]\to x=e^{3y-1}[/tex]
Solve for [tex]y, x=e^{3y-1}[/tex]
Therefore, the answer is [tex]\frac{\log(x)+1}{3}[/tex].
Learn more about the inverse function:
brainly.com/question/13671128
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.